Dinamika Pembaharuan Batas Usia Perkawinan (Analisis Batas Umur Melangsungkan Pernikahan Dalam Hukum Nasional Indonesia) - Riska Yunitasari Yunitasari (DOKTRINA: JOURNAL OF LAW, 2020)
This paper reviews the dynamics of age limits in marriage. The purpose of the research regarding the historicity of the formation of Law No. 1 of 1974 concerning Marriage, the age limit of marriage according to the Qur'an, hadith and ulamamadzhab, the concept of maturity to carry out marriage according to Law No. 1 of 1974 and review the child protection law against the provisions of Law No. 1 of 1974 concerning the Minimum Age for Marriage. This research method uses a qualitative method that is a literature study, this is related to things that focus on the problem of the ideal limit of marriage. The results found are inconsistencies in the marriage age limit in the legislation, where in Article 7 paragraph (1) of Law Number 1 of 1974 concerning marriage it is stated that the maturity of a child is if a man is 21 years old and a woman is 18 years old year. In Article 7 paragraph (1) of Law No. 1 of 1974 concerning marriage it is stated that marriage is only permitted if men have reached the age of 19 years and women have reached the age of 16 years.